Time present and time past : a duration analysis of IMF program spells - Joseph P. Joyce (Wellesley College, Department of Economics, 2001)
The programs of the International Monetary Fund were originally designed to provide short-term assistance to countries implementing policies to address balance of payments disequilibria. In recent decades, however, the Fund has instituted new facilities with longer time horizons, while many developing countries have adopted consecutive programs. As a result, the length of time spent by countries in IMF programs has grown, and in some cases has extended over a decade. This paper analyzes the IMF program spells for a group of emerging economies over the period of 1982 to 1997. Duration models are used to investigate the time dependence of the failure rate of the spells and the factors that affect the duration of program spells. The hazard ratio of program spells has a non-monotonic shape, first rising and then falling over time. Program duration is extended for those countries with lower per-capita income, exports concentrated in primary goods, landlocked geographic status, and stable legal processes.
Keywords: F3; 330; Internationaler Kredit; Anpassungsprogramm des IWF; Dauer; Entwicklungsländer